La incidencia de la pandemia del COVID-19 en el análisis de los precios de transferencia para efecto del impuesto a la renta en el Perú: medidas requeridas - Villagra Cayamana, Renée Antonieta (2022)
This paper analyzes the incidence in our country of the recommendations provided by the OECD in its Guide on the implications of the COVID-19 Pandemic on transfer pricing Guidance on the transfer pricing implications of the COVID-19 pandemic published on December 18, 2020 and which represents the consensus perspective of the more than 137 members of the BEPS Inclu-sive Framework, among which is Peru, regarding the application of the arm’s length principle for problems generated or exacerbated by the pandemic. In particular, the problem of comparability analysis is evaluated in a scenario of lack of comparable transactions and companies in the 2020 and subsequent years affected by the pandemic. Likewise, the issue of losses is addressed from two perspectives, those as a comparable result and the generation of losses in business models with limited risk. It is concluded that several of the measures recommended by the Inclusive Framework can be materialized through the flexibility and openness of the Tax Administration in audits; however, allowing the modification of the transfer pricing analysis reflected in the Local Report based on information of comparable companies obtained later requires the issuance of a legal norm that does not condition the rectifying return to the verification of SUNAT and tempo-rarily avoid the application of infractions and sanctions for the declaration of false data.